Scientific books, illustrated knowledge and reading seditious conduct in the luís vieira da silva canon's library (Minas Gerais, Brazil, 1789) - Rodrigues, André Figueiredo [UNESP] (Instituto de Investigaciones Dr. Jose Maria Luis Mora, 2020)
The article analyzes the presence of books with themes related to Science and the illustrated knowledge in the library of the canon Luís Vieira da Silva, one of those implicated in the Inconfidência Mineira of 1789. In the context discusses the relation of his books, local bodies of knowledge and some “seditious” reading practices, provided by the revolutionary ideas that circulated in Minas Gerais in the second half of the eighteenth century, coming from Europe and North America.
Livros científicos, saberes ilustrados e condutas “sediciosas” de leitura na livraria do cônego Luís Vieira da Silva (Minas Gerais, Brasil, 1789)
Keywords: Inconfidência Mineira; Reading practices; Scientific books; Seizure-books